Stability analysis of laterally loaded trees based on tree-root-soil interaction - Kim, Yongmin (2021)
This paper presents the development of a numerical model for simulating tree stability considering tree-root-soil interaction. This model is validated against tree pulling test results for three tree species by comparing the derived load-deflection curves from the numerical model with those obtained from the field experiments. Experimental overall stiffness of a tree is calculated based on the tree pulling tests and is implemented in the numerical simulations. A series of numerical tree stability analyses for a tree with various geometries and properties is performed to investigate the effects of influencing parameters on the lateral resistance behavior of the trees. Through comparison with the results of tree pulling tests, the three-dimensional (3D) numerical results from the present study is found to be in good agreement with the general trend observed from the field measurements and thus, the numerical model represents a realistic tree-root-soil interaction for laterally loaded trees. In addition, numerical analysis results confirm the fact that the lateral behavior of the tree is strongly dependent on the tree geometries (i.e., trunk diameter and rooting depth), and elastic modulus of trees and soils.